Effectivity of homecare and professional biofilm removal procedures on initial supragingival biofilm on laser-microtextured implant surfaces in an ex vivo model - Gordon John; Frank Schwarz; Alexandra Kravchenko; Michelle Alicia Ommerborn; Jürgen Becker (SpringerOpen, 2021)
Abstract Background The aim of the current study was the evaluation of initial biofilm adhesion and development on laser-microtextured implant collar surfaces and the examination of effectivity of different biofilm management methods. Methods Initial biofilm formation was investigated on hydrophobic machined and laser-microtextured (Laser-Lok) titanium surfaces and hydrophobic machined and laser-microtextured (Laser-Lok) titanium aluminium vanadium surfaces and compared to hydrophobic smooth pickled titanium surfaces, hydrophilic smooth and acid etched titanium surfaces, hydrophobic sandblasted large grid and acid etched titanium surfaces (titanium Promote) via erythrosine staining and subsequent histomorphometrical analysis and scanning electron microscopic investigations. After decontamination procedures, performed via tooth brushing and glycine powder blasting, clean implant surface was detected via histomorphometrical analysis. Results After 24 h mean initial plaque area was detected in the following descending order: smooth pickled titanium > titanium Promote > hydrophilic smooth and acid etched titanium > Laser-Lok titanium > Laser-Lok titanium aluminium vanadium. The same order was determined after 48 h of biofilm formation. After glycine powder blasting all samples depicted almost 100% clean implant surface. After tooth brushing, Laser-Lok titanium (67.19%) and Laser-Lok titanium aluminium vanadium (69.80%) showed significantly more clean implant surface than the other structured surfaces, hydrophilic smooth and acid etched titanium (50.34%) and titanium Promote (33.89%). Smooth pickled titanium showed almost complete clean implant surface (98.84%) after tooth brushing. Conclusions Both Laser-Lok surfaces showed less initial biofilm formation after 24 and 48 h than the other implant surfaces. In combination with the significant higher clean implant surfaces after domestic decontamination procedure via tooth brushing, both Laser-Lok surfaces could be a candidate for modified implant and abutment designs, especially in transmucosal areas.